Association between polypharmacy and falls in older adults: a longitudinal study from England - Nafeesa N Dhalwani; Melanie J Davies; Kamlesh Khunti; Harini Sathanapally; Radia Fahami; Sam Seidu (BMJ Open)
Objectives Assess the longitudinal association between polypharmacy and falls and examine the differences in this association by different thresholds for polypharmacy definitions in a nationally representative sample of adults aged over 60 years from England.Design Longitudinal cohort study.Setting The English Longitudinal Study of Ageing waves 6 and 7.Participants 5213 adults aged 60 or older.Main outcome measures Rates, incidence rate ratio (IRR) and 95% CI for falls in people with and without polypharmacy.Results A total of 5213 participants contributed 10 502 person-years of follow-up, with a median follow-up of 2.02 years (IQR 1.9–2.1 years). Of the 1611 participants with polypharmacy, 569 reported at least one fall within the past 2 years (rate: 175 per 1000 person-years, 95% CI 161 to 190), and of the 3602 participants without polypharmacy 875 reported at least one fall (rate: 121 per 1000 person-years, 95% CI 113 to 129). The rate of falls was 21% higher in people with polypharmacy compared with people without polypharmacy (adjusted IRR 1.21, 95% CI 1.11 to 1.31). Using ≥4 drugs threshold the rate of falls was 18% higher in people with polypharmacy compared with people without (adjusted IRR 1.18, 95% CI 1.08 to 1.28), whereas using ≥10 drugs threshold polypharmacy was associated with a 50% higher rate of falls (adjusted IRR 1.50, 95% CI 1.34 to 1.67).Conclusions We found almost one-third of the total population using five or more drugs, which was significantly associated with 21% increased rate of falls over a 2-year period. Further exploration of the effects of these complex drug combinations in the real world with a detailed standardised assessment of polypharmacy is greatly required along with pragmatic studies in primary care, which will help inform whether the threshold for a detailed medication review should be lowered.